Performance study of close-loop power control algorithms for a cellular CDMA system - Sim, Moh Lim; Gunawan, Erry; Song, Boon Hee; Soh, Cheong Boon (IEEE Vehicular Technology Society, 1999)
Performance of a reverse link code-division multiple-access (CDMA) system with fast close-loop power control algorithms is studied. It is found that if fast close-loop power control algorithm functions effectively, the speed of the mobile unit is in the range such that its Doppler frequency is less than one tenth of the power control updating rate. This paper also proposes a new predictive power control algorithm with better performance in terms of system capacity than the conventional and adaptive step size algorithms. An increase in system capacity as high as 22% compared with the conventional algorithm can be achieved depending on the mobile velocity.